2020
DOI: 10.1093/jxb/eraa226
|View full text |Cite
|
Sign up to set email alerts
|

Type II Fusarium head blight susceptibility conferred by a region on wheat chromosome 4D

Abstract: Fusarium head blight (FHB) causes significant grain yield and quality reductions in wheat and barley. Most wheat varieties are incapable of preventing FHB spread through the rachis, but disease is typically limited to individually infected spikelets in barley. We point-inoculated wheat lines possessing barley chromosome introgressions to test whether FHB resistance could be observed in a wheat genetic background. The most striking differential was between 4H(4D) substitution and 4H addition lines. The 4H addit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
(59 reference statements)
1
19
0
Order By: Relevance
“…The observed abundance decrease of these two proteins could suggest a fungal manipulation of this defense process that enhances wheat susceptibility independently of the plant and fungal genetics. Although the study of only three wheat cultivars with three F. graminearum strains is not sufficient to generalize these observations, the absence of specific responses in these candidate susceptibility genes echoes the already stated hypothesis of Hales et al (2020) suggesting that the wheat susceptibility to FHB could be common to a wide range of current cultivars. Our results further complement this hypothesis by suggesting that the molecular determinants of FHB susceptibility may also be unspecific to the fungal strain.…”
Section: Interaction Is Based On a Core Dual Proteomementioning
confidence: 82%
See 1 more Smart Citation
“…The observed abundance decrease of these two proteins could suggest a fungal manipulation of this defense process that enhances wheat susceptibility independently of the plant and fungal genetics. Although the study of only three wheat cultivars with three F. graminearum strains is not sufficient to generalize these observations, the absence of specific responses in these candidate susceptibility genes echoes the already stated hypothesis of Hales et al (2020) suggesting that the wheat susceptibility to FHB could be common to a wide range of current cultivars. Our results further complement this hypothesis by suggesting that the molecular determinants of FHB susceptibility may also be unspecific to the fungal strain.…”
Section: Interaction Is Based On a Core Dual Proteomementioning
confidence: 82%
“…By definition, any plant gene that facilitates infection and that promotes compatibility with pathogens can be considered as a susceptibility gene (van Schie and Takken, 2014). Formally (Li et al, 2019;Su et al, 2019;Brauer et al, 2020;Su et al, 2021) or indirectly identified (Ma et al, 2006;Basnet et al, 2012;Garvin et al, 2015;Hales et al, 2020), the deletion of these genes coding for the so-called susceptibility factors may provide a complementary approach to the introgression of gain-of-function resistance genes (Fabre et al, 2020;Moniruzzaman et al, 2020;Gorash et al, 2021). However, despite these attempts to elucidate the molecular processes involved both in wheat resistance and susceptibility to FHB, understanding this interaction still requires many efforts, in particular by reconciling information from the two partners of this pathosystem.…”
Section: Introductionmentioning
confidence: 99%
“…For the last twenty years, the multiple evidences of the role of a plant's susceptibility factors in promoting pathogen infection have opened new opportunities to identify such pivotal determinants of plant diseases, and a number of studies already reported that mutation or loss of susceptibility genes can be used in resistance breeding [16,17]. With the increasing evidences of the role of wheat's susceptibility factors in FHB development [18][19][20][21][22][23], elucidating the mechanisms of wheat susceptibility to F. graminearum appears as a promising approach to improve FHB resistance [17,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of genomic level, the researches on FHB in recent decades has provided us with abundant information for genetic and molecular determinants, mainly focusing on the resistant genetic components. Recent reports demonstrated that the removal of the susceptibility interval on the short arm of chromosome 4D [153] and the deletion of Sf-Fhb7AS enhanced Type II resistance to FHB [154]. Therefore, in addition to finding the components or pathway related to disease resistance through the analysis of omics data, knocking out or knocking down the expression host susceptibility genes has provided new venues for protection against pathogens [155].…”
Section: Challenges and Prospectivesmentioning
confidence: 99%